Clinical and economic analysis of the modern strategies for treating metabolic syndrome - Marina Fedorovna Kalashnikova; Vera Uchamprina; Tatiana Ivanovna Romantsova; Andrey Nikolaevich Gerasimov (Сахарный диабет)
Objective. The objective of this study was to identify the ways to optimize therapy for metabolic syndrome through complex clinical and economic analysis. Methods. Sixty patients with metabolic syndrome were included in the study. The study group (30 subjects with the mean age of 41.0?11 years, 23 females (76.7%), 7 males (23.3%)) received pharmacotherapy for obesity (orlistat) and insulin resistance (metformin), lipid-lowering therapy and antihypertensive therapy, if needed. The control group (30 patients with the mean age of 43.4?9.5 years, 26 females (86.7%), 4 males (13.3%)) received lipid-lowering and antihypertensive therapy, if needed. All patients underwent clinical and laboratory examination, assessment of depression (Beck Depression Inventory) and evaluation of the quality of life using the SF-36 questionnaire at admission to the study and after 6 months of therapy. Complex clinical and economic analyses, including cost-effectiveness and cost-utility analyses and calculation of such indices as ?the incremental cost-effectiveness ratio? (ICER), LYG, QALY and ?net monetary benefit? (NMB), were conducted based on the results obtained. Results. Improvement of clinical and laboratory indicators and quality of life in the study group was more significant than that in the control group. The direct medical costs were 33,440.40 RUB for the study group and 18,878.50 RUB for the control group (for 6 months of therapy). The control group CER was 4,016.70, while the study group CER was 3,125.30; ICER was 2,430.90 RUB. LYG was equal to 0.7 and 2.3 years for the control and the study groups, respectively. The QALY measure for the control and study groups was 8.63 and 9.45, respectively. The weighted average total costs for the intended period of living was 498,745.00 RUB for the control group and 457,866.00 RUB for the study group. The control group CUR was 57,792.00 and 54,902.00 RUB/QALY without and with discounting, respectively, while in the study group they were 48,451.00 and 46,029.00 RUB/QALY, respectively. The NMB for the control group amounted to 10,790,910.00 and 10,815,840.00 RUB without and with discounting, respectively, while for the study group the values were 11,904,500.00 and 11,927,390.00 RUB. Conclusions. The results of clinical and economic analysis show that treatment of the metabolic syndrome, including pharmacotherapy of obesity and insulin resistance, should be prioritized over mere medical advisory and lifestyle modifications.